2008
DOI: 10.1007/s10995-008-0319-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intermittent Preventive Treatment of Malaria with Sulphadoxine-pyrimethamine in Preventing Anaemia in Pregnancy among Nigerian Women

Abstract: The IPT regime with sulphadoxine-pyrimethamine is an effective, practicable strategy to decrease risk of anaemia in women of low parity residing in areas endemic for malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 16 publications
4
25
1
2
Order By: Relevance
“…2 Malaria as a cause of anaemia in our study is rather unlikely because during antenatal care, all women in our study received malaria intermittent prophylaxis with sulphadoxinepyrimethamine regimen, were given insecticide-treated bednets, and received prompt and active treatment of acute malaria cases. In support of this argument, Asa et al 24 observed that a sulphadoxine-pyrimethamine regimen is an effective, practicable strategy to decrease the risk of anaemia in women of low parity residing in areas endemic for malaria. Though a statistically significant relationship was found only between women's education and SR (P ¼ 0.032), booking status correlated with SR and haemoglobin groupings in our study.…”
Section: Discussionmentioning
confidence: 97%
“…2 Malaria as a cause of anaemia in our study is rather unlikely because during antenatal care, all women in our study received malaria intermittent prophylaxis with sulphadoxinepyrimethamine regimen, were given insecticide-treated bednets, and received prompt and active treatment of acute malaria cases. In support of this argument, Asa et al 24 observed that a sulphadoxine-pyrimethamine regimen is an effective, practicable strategy to decrease the risk of anaemia in women of low parity residing in areas endemic for malaria. Though a statistically significant relationship was found only between women's education and SR (P ¼ 0.032), booking status correlated with SR and haemoglobin groupings in our study.…”
Section: Discussionmentioning
confidence: 97%
“…25 Although anemia remains a major challenge in sub-Sahara Africa, malaria is an important contributor to maternal and perinatal morbidity and mortality in these countries. 10 The WHO currently recommends that each pregnant woman should receive IPTp-SP at each ANC visit after quickening, which in practice leads to two or three doses during the course of the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…10,15,17,18,27,28 This policy has been adopted by most countries in Africa, but implementation has been suboptimal. 29 Furthermore, the spread of SP-resistant P. falciparum reinforces the importance of investigating the ongoing effectiveness of IPTp-SP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations